2008
DOI: 10.1029/2007gl032680
|View full text |Cite
|
Sign up to set email alerts
|

Ice core record of rising lead pollution in the North Pacific atmosphere

Abstract: A high‐resolution, 8000 year‐long ice core record from the Mt. Logan summit plateau (5300 m asl) reveals the initiation of trans‐Pacific lead (Pb) pollution by ca. 1730, and a >10‐fold increase in Pb concentration (1981–1998 mean = 68.9 ng/l) above natural background (5.6 ng/l) attributed to rising anthropogenic Pb emissions from Asia. The largest rise in North Pacific Pb pollution from 1970–1998 (end of record) is contemporaneous with a decrease in Eurasian and North American Pb pollution as documented in ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 24 publications
8
127
1
Order By: Relevance
“…The cylindrical ice core was cut into five parallel longitudinal samples, each with Ϸ3.3 ϫ Ϸ3.3-cm cross-section (24,25). We used two high-resolution inductively coupled plasma mass spectrometers (HR-ICP-MS) connected in parallel to a continuous ice core-melter system to make repeat measurements of the isotopes 23 Na, 140 Ce, 111 Cd, 205 Tl, and 208 Pb, with only the innermost 10% of the longitudinal samples used for elemental and BC analyses (18,24,25). BC was measured by using a laser-based atmospheric analyzer (18).…”
Section: Methodsmentioning
confidence: 99%
“…The cylindrical ice core was cut into five parallel longitudinal samples, each with Ϸ3.3 ϫ Ϸ3.3-cm cross-section (24,25). We used two high-resolution inductively coupled plasma mass spectrometers (HR-ICP-MS) connected in parallel to a continuous ice core-melter system to make repeat measurements of the isotopes 23 Na, 140 Ce, 111 Cd, 205 Tl, and 208 Pb, with only the innermost 10% of the longitudinal samples used for elemental and BC analyses (18,24,25). BC was measured by using a laser-based atmospheric analyzer (18).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, both the Eclipse and PRC records show a renewed rise in Pb deposition after the mid-1990s. Osterberg et al (2008) contend that the PRC ice-core Pb record reflects increasing industrial emissions and trans-Pacific transport of polluted outflow from the rapidly industrializing sectors of eastern Asia (particularly China), an interpretation supported by the sharply rising pattern of SO 2 emissions from this region (Fig. 6d).…”
Section: Findings From the 2001 -02 Cores: Evidence For Transpacific mentioning
confidence: 90%
“…Logan, based on aluminium (Al) concentrations in snow and firn, showed that crustal elements may be contributed by long-range dust transport as well as by fallout from volcanic eruptions (Matoba and Shiraiwa, 2005). More recently, Osterberg et al (2008) produced an 8000-year-long, high-resolution record of major ions and trace elements from the Mt. Logan PRC core.…”
Section: Long-range Transport Of Asian Desert Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither CC nor LPD techniques provide associated information on particle composition or morphology; broad assumptions of both parameters are thus required to infer ice core dust concentrations from these instruments. Alternate online techniques, such as inductively coupled plasma mass spectrometry (ICP-MS) and ion chromatography (IC), are also routinely used to determine elemental (e.g., Cd, Ce, Zn, Pb) and soluble ion (e.g., Na + , SO 2− 4 , NH + 4 ) concentrations in ice cores, providing independent indices of past dustiness (e.g., Rhodes et al, 2011), and anthropogenic particle emissions (e.g., Osterberg et al, 2008;McConnell and Edwards, 2008). Albeit analytically precise, ICP-MS and IC rely on techniques that analyze only a portion of aerosols in an aqueous suspension/solution and not the properties of the progenitor aerosols themselves, i.e., particulate morphology or size.…”
Section: Introductionmentioning
confidence: 99%